PELAKSANAAN PEMBEAJAR DARING MASA PANDEMI COVID-19 PADA MATA PELAJARAN EKONOMI KELAS XI - Irfan Dea; Nuraini Asriati; Warneri Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
ABSTRACTThis thesis is entitled "Implementation of Online Learning During the Covid-19Pandemic in Economics Subject Class XI IIS IN SMA Islam BawariPontianak". The problem in this research is how to implement online learningduring the covid-19 pandemic in the economics subject of class XI IIS atBawari Islamic High School Pontianak. The method used is descriptivemethod. The form of research is qualitative description. Data collectiontechniques in this study are: direct communication with data collection tools,interview guides, direct observation with data collection tools, observationsheets, documentary studies with data collection tools, data archives. With thefollowing research results: Based on the results of the research on theImplementation of Online Learning during the Covid-19 Pandemic inEconomics Subject Class XI IIS IN SMA Islam Bawari Pontianak, it can besaid that it is going well and in terms of sub-problems, it can be concluded: 1)That the Planning of Online Learning Period The Covid-19 pandemic in theClass XI IIS Economics Subject at the Bawari Islamic High School inPontianak is going well. 2) That the implementation of online learning duringthe Covid-19 pandemic in the Class XI IIS Economics Subject at the BawariIslamic High School, Pontianak, was carried out well. 3) That the evaluation ofOnline Learning during the Covid-19 Pandemic in Economics Class XI IISSubjects at Bawari Islamic High School Pontianak, for teacher assessment andevaluation using the Whatsapp application.Keywords : Bawari Islamic High School Pontianak, Economics Subject,Implementatation of Online